2016
DOI: 10.1002/pola.28240
|View full text |Cite
|
Sign up to set email alerts
|

Highly symmetric single nickel catalysts bearing bulky bis(α-diimine) ligand: Synthesis, characterization, and electron-effects on copolymerization of norbornene with 1-alkene at elevated temperarure

Abstract: Three new three‐dimensional geometry bulky α‐diimine ligands (L) containing electron‐donating and electron‐withdrawing groups, 9,10‐dihydro‐9,10‐ethanoanthracene‐11,12‐di(Ar)imine (Ar = p‐PhCH3, L1; Ar=p‐PhCl, L2; Ar=p‐PhCF3, L3.), and their corresponding single Ni(II) catalysts,NiL2Br2 (Ni(L1)2Br2, Ni(L2)2Br2, and Ni(L3)2Br2, were synthesized and the molecular structure were determined by X‐ray crystallography. All NiL2Br2 catalysts were tested for norbornene polymerization and copolymerization of norbornene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Three-dimensional geometry Ni-and Pd-based α-diimine complexes with a bulky bridged backbone. [105][106][107][108][109][110][111] played high thermal stability, high activities of up to 3.2 × 10 6 g PE (mol Pd h) −1 (60°C, 15 min), and high polymer M n (up to 538 000) in ethylene polymerization. More interestingly, semicrystalline low-density branched (23-29/1000 C) PEs with high T m of up to 99°C were obtained.…”
Section: Fig 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional geometry Ni-and Pd-based α-diimine complexes with a bulky bridged backbone. [105][106][107][108][109][110][111] played high thermal stability, high activities of up to 3.2 × 10 6 g PE (mol Pd h) −1 (60°C, 15 min), and high polymer M n (up to 538 000) in ethylene polymerization. More interestingly, semicrystalline low-density branched (23-29/1000 C) PEs with high T m of up to 99°C were obtained.…”
Section: Fig 17mentioning
confidence: 99%
“…17) containing a bulky bis(α-diimine) ligand. 109,110 These catalysts demonstrated high thermal stability and high catalytic activity toward NB polymerization. They also studied a related 6,13-dihydro-6,13-ethanopentacenebased nickel complex C34 (Fig.…”
Section: Modifications Of the α-Diimine Backbone Structuresmentioning
confidence: 99%
“…It has been reported that PNB obtained by nickel catalysts could be dissolved in chlorobenzene at room temperature in the 2000s, and the solubility and processability of PNB have been improved. 5,7 Introducing polar groups [8][9][10][11] or exible chains 12,13 into the PNB backbone has become an effective means of solving the problem. The design and synthesis of particularly efficient and stable catalysts is very important for the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the further development of norbornene is hampered by its poor bond properties, low solubility and poor mechanical properties. At present, the introduction of polar groups [18][19][20] or exible chains [21][22][23][24][25] on the norbornene backbone is the most effective means to solve this problem. In order to achieve this goal, it is important to synthesize some efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Norbornene is a typical cycloolen with many advantages of cycloolens, but due to the presence of bicyclic skeletons in the polymer, it is brittle and has a small elongation at break. In order to improve its defects, the copolymer obtained by copolymerizing norbornene with a-olen 22,23,36 not only can reserve the heat resistance and dimensional stability of polynorbornene, but also has excellent optical properties, good processing and solubility, which has attracted scholars's attention at both home and abroad. For example, Kaminsky group 37 achieved the copolymerization of norbornene with ethylene using a metallocene catalyst.…”
Section: Introductionmentioning
confidence: 99%